Cardiovascular Outcomes in Acute Coronary Syndrome and Malnutrition - Lai, Angeline RX; Warrier, Manish; Ng, Ethel ZX; Lin, Chaoxing; Chin, Yip Han; Kong, Gwyneth; Anand, Vickram V.; Lee, Ethan CZ; Lai, Haoxing; Ng, Hung Wei; Goh, Rachel SJ; Chong, Bryan; et al. (JACC. Advances (Online), 2023)
There is emerging evidence that malnutrition is associated with poor prognosis among patients with acute coronary syndrome (ACS). This study seeks to elucidate the prognostic impact of malnutrition in patients with ACS and provide a quantitative review of most commonly used nutritional assessment tools. Medline and Embase were searched for studies reporting outcomes in patients with malnutrition and ACS. Nutritional screening tools of interest included the Prognostic Nutrition Index, Geriatric Nutritional Risk Index, and Controlling Nutritional Status. A comparative meta-analysis was used to estimate the risk of all-cause mortality and cardiovascular events based on the presence of malnutrition and stratified according to ACS type, ACS intervention, ethnicity, and income. Thirty studies comprising 37,303 patients with ACS were included, of whom 33.5% had malnutrition. In the population with malnutrition, the pooled mortality rate was 20.59% (95% CI: 14.95%-27.67%). Malnutrition was significantly associated with all-cause mortality risk after adjusting for confounders including age and left ventricular ejection fraction (adjusted HR: 2.66, 95% CI: 1.78-3.96, P = 0.004). There was excess mortality in the group with malnutrition regardless of ACS type (P = 0.132), ethnicity (P = 0.245), and income status (P = 0.058). Subgroup analysis demonstrated no statistically significant difference in mortality risk between individuals with and without malnutrition (P = 0.499) when using Controlling Nutritional Status (OR: 7.80, 95% CI: 2.17-28.07, P = 0.011), Geriatric Nutritional Risk Index (OR: 4.30, 95% CI: 2.78-6.66, P < 0.001), and Prognostic Nutrition Index (OR: 4.67, 95% CI: 2.38-9.17, P = 0.023). Malnutrition was significantly associated with all-cause mortality risk following ACS, regardless of ACS type, ethnicity, and income status, underscoring the importance of screening and interventional strategies for patients with malnutrition. [Display omitted]